2022
DOI: 10.1021/acsomega.2c02112
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Application of Low-Field Nuclear Magnetic Resonance Technology in Coalbed Methane Production Simulation

Abstract: Low-field nuclear magnetic resonance has become one of the main methods to characterize static parameters and dynamic changes in unconventional reservoirs. The research focus of this paper is process simulation of coalbed methane (CBM) production. The dynamic variation of pore volume with different pore sizes during pressure drop, methane desorption–diffusion process, and methane–water interaction during migration is discussed. Moreover, the calculation principles of NMR single and multifractal models are syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Direct and indirect technologies have been developed to analyze shale pore structures . According to the direct method, qualitative information of pore structure, such as pore type and morphology in two/three-dimension, can be described well. The indirect technologies are applied to obtain information about the quantitative parameters of shale pore structures, such as porosity, permeability, specific surface area (SSA), and PSD. …”
Section: Introductionmentioning
confidence: 99%
“…Direct and indirect technologies have been developed to analyze shale pore structures . According to the direct method, qualitative information of pore structure, such as pore type and morphology in two/three-dimension, can be described well. The indirect technologies are applied to obtain information about the quantitative parameters of shale pore structures, such as porosity, permeability, specific surface area (SSA), and PSD. …”
Section: Introductionmentioning
confidence: 99%
“…Coalbed methane (CBM), an important, nontraditional, clean energy resource, exists in coal seams in a free, adsorbed, solid-solution and dissolved state and mainly exists in an adsorbed state in coal matrices. In CBM recovery or gas drainage prior to coal mining, gas desorbs from the wall of the pores in the coal matrix and diffuses through the pore system to the cleat due to the difference of gas concentration, then flows to the production well or drainage borehole through the cleat system due to a pressure difference. , Hence, the desorption characteristics of coal are key factors to CBM extraction. …”
Section: Introductionmentioning
confidence: 99%
“… 1 3 In CBM recovery or gas drainage prior to coal mining, gas desorbs from the wall of the pores in the coal matrix and diffuses through the pore system to the cleat due to the difference of gas concentration, then flows to the production well or drainage borehole through the cleat system due to a pressure difference. 4 , 5 Hence, the desorption characteristics of coal are key factors to CBM extraction. 6 8 …”
Section: Introductionmentioning
confidence: 99%
“…LF-NMR inverts the fluid content, properties, and distribution and fluid pore size information by injecting a 1 H-containing fluid (water, methane) into porous media and testing its relaxation process under an external magnetic field. Therefore, LF-NMR can well characterize the water micro-occurrence characteristics in coal under different S w . Additionally, LF-NMR can also simulate the in situ coal seam environment through the corresponding temperature and pressure application instruments and fluid injection system and reflect the changes in coal pore structure and fluid transport under complex formation conditions. Lu et al indicated that during hydraulic fracturing, the formation of new pores was caused by broken pore walls that were supported by the injection liquid and pore water. Zhao et al .…”
Section: Introductionmentioning
confidence: 99%